Strategi Intervensi Penanganan Stunting di Indonesia: Studi Literatur - Silvia Anggraini; Muthmainnah Muthmainnah; Nurul Septiani; Tomy Suganda (Pelantar Press, 2024)
Stunting not only has an impact on children's physical growth and development, but also has significant long-term implications for the quality of Indonesia's human resources (HR) in the future. Comprehensive and multi-sectoral stunting management efforts involving various parties need to be carried out. To analyze more deeply the intervention strategies that have been implemented in efforts to deal with stunting in Indonesia as a form of identifying approaches that have been proven successful and are relevant for the Indonesian context. This research uses the PRISMA literature review, through a digital library database that is connected to various scientific publication pages through keywords such as